Hanoi’s septic tanks – technology of a city in flow from the late 19th century till today - Schramm, Sophie (International Planning History Society Proceedings, 2016)
Septic tanks and their simple and stable brick structures contrast the highly complex and dynamic social and material processes within and outside them. Bacteria digest wastewaters and permanently change their composition as they flow from the households through the tanks and the city. Humans shape these dynamics as they build houses, re-construct tanks and drainage systems and with their practices regarding the maintenance of the tanks or their neglect. Septic tanks were central to French colonial sanitation planning in Hanoi. From the end of the 19th century on they were supposed to replace the then predominant night-soil system which French engineers deemed a „défi aux règles d´hygiène les plus élémentaires” and thus to bring a specific order to the city’s sanitary situation. Sanitation planning involved not only the decentralised tanks installed under individual buildings and respective practices, but a city wide re-ordering of material flows with the centralised treatment of septage sludge and the generation of bio-gas. In contrast, current large-scale sanitation interventions and planning largely neglect septic tanks and attempt to bring order to sanitation in Hanoi with the installation of „central large-scaled wastewater treatment plants”. However, today septic tanks are spread throughout Hanoi; they have become the city’s predominant means of sanitation. This paper examines the history of septic tanks in Hanoi regarding engineers’ and planners’ ideas and imaginations focusing on the late 19th century and the past decade until today. It contrasts the imaginations of the 19th century with the actual technology that became known as the septic tank in Hanoi and respective practices, which deviate from original planning in place-specific ways within the city. Hanoi’s septic tanks of today defeat planners’ imaginations of urban order as they even incorporate elements of the historic night-soil system dismissed by urban engineers since French colonial era. They produce particular dis-orders, which transcend urban-rural boundaries and are constitutive of Hanoi’s urbanisation dynamics with blurred and constantly changing passages between urban and rural rather than fixed threshold. This paper conceptualises Hanoi’s septic tanks as elements in broader urban sociotechnical ensembles, which constantly change but at the same time perpetually resist formal planning, and their interrelations with urbanisation dynamics from colonial times to present.